2015
DOI: 10.1038/eye.2014.318
|View full text |Cite
|
Sign up to set email alerts
|

Minimal incision posterior approach levator plication for aponeurotic ptosis

Abstract: Purpose To assess the efficacy and predictability of a minimal incision posterior approach levator plication technique for correction of involutional ptosis. Method Retrospective chart review of patients with involutional aponeurotic ptosis underwent minimal incision posterior approach levator plication technique between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In study by DS Ng et al, [9] "44 lids of 27 patients were included. Preoperative mean MRD was 0.48 ± 0.56mm.…”
Section: Resultsmentioning
confidence: 99%
“…In study by DS Ng et al, [9] "44 lids of 27 patients were included. Preoperative mean MRD was 0.48 ± 0.56mm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have observed that once attached to the aponeurosis, the potentially exposed suture is rotated superiorly and the upper border of the tarsus rotates forward, reducing the potential to abrade the cornea. Only one previous small series 7 reports outcomes of moderate-to-severe ptosis using a posterior approach technique. This also involved septal-sparing advancement of the aponeurosis in 27 predominantly Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Posterior approach ptosis surgery has traditionally been reserved for mild-moderate involutional blepharoptosis with good levator excursion with only one small series reporting outcomes in more severe ptosis. 7 We present a retrospective review of an interventional case series, not reported in any previous study, of severe involutional ptosis and outcomes using a posterior approach white-line levator advancement technique.…”
Section: Introductionmentioning
confidence: 99%
“…The range of the upper eyelid margin covering the cornea is based on the degree of upper eyelid margin covering the upper edge of cornea after the effects of frontalis muscle were ruled out. A range of not more than 4 mm indicates mild ptosis, a range of not more than 6 mm indicates moderate ptosis and a range larger than 6 mm and covering the center of the pupil indicates severe ptosis [8] .…”
mentioning
confidence: 99%